Gastronomic paradigm shifts revisited: from culinary abstraction to a post-digital integrative cuisine - del Moral, Raimundo G. (Frontiers in Nutrition, 2025)
This article proposes the existence of a fifth gastronomic paradigm, which we term Post-Digital Integrative Cuisine, marking an epistemological rupture in the evolution of Western haute cuisine. Drawing on Kuhnian theory, regenerative ethics, and interdisciplinary case studies, we argue that this paradigm is defined not by stylistic or technical novelty, but by its reconfiguration of gastronomy as a multispecies, systemic, and anticipatory practice. This model integrates microbial fermentation, biotechnological innovation, ancestral knowledge, and artificial intelligence into culinary design. It prioritizes ecological regeneration, distributed authorship, and epistemic pluralism over individual genius or sensory spectacle. Empirical examples illustrate how food becomes a medium for world-making, narrative design, and regenerative aesthetics. We analyze how this paradigm realigns culinary aesthetics with ethical and ecological values through principles such as circular gastronomy, fermentation as epistemology, dematerialized luxury, and AI-assisted creativity. At the same time, we critically assess persistent tensions: the risk of elitism, techno-solutionism, and symbolic commodification. Key contributions include (1) a Kuhnian mapping of gastronomic paradigms, (2) a conceptual definition of the fifth paradigm's post-disciplinary logic, and (3) an exploration of anticipatory imagination and food as a speculative design tool. By situating gastronomy within the frameworks of environmental humanities, futures studies, and hybrid knowledge systems, this article reframes haute cuisine as a cultural technology for ecological care, multispecies justice, and epistemic transformation. The Post-Digital Integrative Cuisine is not a utopian projection but a distributed present—demanding visionary courage, ethical coherence, and systemic participation.